Moral Collapse and State Failure: A View From the Past - Blanton, Richard E.; Feinman, Gary M.; Kowalewski, Stephen A.; Fargher, Lane F. (Frontiers in Political Science, 2020)
Abstract We have found that collective action theory, as developed by Margaret Levi and others, provides a new direction for the study of growth and decline of premodern states. By following this lead, we have challenged the traditional consensus that despotic rule characterized most premodern states, demonstrating instead the existence of a state-building process in which fiscal economies of joint production fostered the implementation of good government such as accountable leadership and public goods. In this paper we focus attention on causes and consequences of state decline, highlighting the decline pattern found where there was good government. Our investigation reveals that while regimes providing good government policies and practices were highly regarded by citizens and brought benefits to them, they were not always highly endurable and regime decline was frequently followed by serious demographic and economic consequences. While causes of decline were varied, we describe and comment on four well-documented examples in which primary causality can be traced to a principal leadership that inexplicably abandoned well-established principles of state-building, while also ignoring their expected roles as effective leaders and moral exemplars.